Exploring the use of digital games as a persuasive tool in teaching Islamic knowledge for Muslim children - Sheikh Abdul Aziz, Madihah; Auyphorn, Panadda; Hamzah, Mohd Syarqawy (The Science and Information Organization, 2019)
Various digital games have been developed that focus on providing a sense of enjoyment and excitement for their players in order to be a modern tool for releasing stress or simply for pleasure. In recent years, digital games were also used for teaching and learning. For example, in History subject, games were used for retelling historical stories; at the same time, to preserve the history for the next generation to learn, understand and appreciate. Similarly, Digital games with Islamic values have also been developed to teach Islamic values or knowledge among players, in other words to persuade players to learn or improve their knowledge on Islam. Many designers assumed that games could be used as a persuasive tool to influence players, to learn and understand Islam as a way of life. However, no prior research has been done on the perception of players before and after playing Islamic digital games. To this end, this paper investigates and reports if Islamic Digital Games could persuade gamers to understanding Islam by exploring the use of these games among gamers. A total of 20 school children voluntarily participated in the experiment and the findings are reported in this paper. The study found positive effects on the users’ perception toward playing digital games embedded with Islamic values.